1995
DOI: 10.1073/pnas.92.25.11480
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of adrenomedullin in rat ischemic cortex and evidence for its role in exacerbating focal brain ischemic damage.

Abstract: Focal brain ischemia is the most common event leading to stroke in humans. To understand the molecular mechanisms associated with brain ischemia, we applied the technique of mRNA differential display and isolated a gene that encodes a recently discovered peptide, adrenomedullin (AM), which is a member of the calcitonin gene-related peptide (CGRP) family. Using the rat focal stroke model of middle cerebral artery occlusion (MCAO), we determined that AM mRNA expression was significantly increased in the ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(94 citation statements)
references
References 36 publications
8
86
0
Order By: Relevance
“…demonstrated that brain ischemia increased AM mRNA expression in rat brain cortex. 8 Hypoxia also induced an increase in AM mRNA expression and protein production in a human colorectal carcinoma cell line. 9 Furthermore, the induction of AM mRNA by hypoxia depends on the transcription factor hypoxia-inducible factor-1 (HIF-1) in human tumor cells.…”
Section: Introductionmentioning
confidence: 92%
“…demonstrated that brain ischemia increased AM mRNA expression in rat brain cortex. 8 Hypoxia also induced an increase in AM mRNA expression and protein production in a human colorectal carcinoma cell line. 9 Furthermore, the induction of AM mRNA by hypoxia depends on the transcription factor hypoxia-inducible factor-1 (HIF-1) in human tumor cells.…”
Section: Introductionmentioning
confidence: 92%
“…Adrenomedullin is a 52-amino-acid peptide belonging to the CGRP family. In rats, adrenomedullin mRNA expression is upregulated after ischemia and may be cerebroprotective, particularly after stroke (Miyashita et al, 2006;Wang et al, 1995). Adrenomedullin increases CBF and prevents ischemia after middle cerebral artery occlusion (Dogan et al, 1997).…”
Section: Figmentioning
confidence: 99%
“…It is synthesized as a 185 amino acid precursor which is processed by consecutive enzymatic steps into a 6000 molecular mass bioactive peptide (Kitamura et al 1993b, Sugo et al 1994. AM production has been characterized in a wide spectrum of tissues, including the cardiovascular (Sakata et al 1993), nervous (Ueta et al 1995, Wang et al 1995, Satoh et al 1996, respiratory (Martínez et al 1995b), endocrine , Satoh et al 1996, renal (Jougaski et al 1994), and digestive systems (Washimine et al 1995). AM mRNA expression is enhanced by inflammatory response elements (interleukin-1 and tumor necrosis factor) and the peptide is markedly up-regulated in the circulation following endotoxin (lipopolysaccharide) challenge or bacterial sepsis (Sugo et al 1995, Hirata et al 1996.…”
Section: Introductionmentioning
confidence: 99%